A Combined Experimental/Computational Study on Adsorption of Fe2+ by Cigarette Filter Added with Chitosan - Sriuttha1, Manop; Chanajaree2, Rungroj; Tongpoothorn3, Wimonrat; Wittayanarakul1, Kitiyaporn (Asian Journal of Chemistry, 2014)
The ability of cigarette filter added with chitosan (CFAC) for the Fe2+ removal from aqueous solution has been investigated by adsorption method. It is found that the Freundlich isotherm can well describe the Fe2+ adsorption capacity in CFAC. The experimental data suggests the pseudo-second-order equation represented as the adsorption model. The Fe2+ ions adsorb spontaneously on the CFAC and the possible process is more favorable at higher temperatures. The obtained DH° and DS° values indicate that the adsorption reaction is the endothermic and some structural changes appear at the adsorbent and randomly occur at the solid/liquid interface, respectively. In addition, the computational approach has been performed to show the binding interaction between the Fe2+ and the chitosan. The result suggests that nitrogen atoms of chitosan are the preferential adsorption site for Fe2+. This work is worth to see the ability of the new adsorbent for further development of metal removal from the aqueous solution that is the application for waste water treatment.